Pharmacokinetics, pharmacodynamics and safety of CKD-519, a CETP inhibitor, in healthy subjects - Kim CO; Oh ES; Choi CG; Kim YJ; Lee S; Kim S; Park MS (Dove Medical Press, 2016)
Choon Ok Kim,1 Eun Sil Oh,2 Chungam Choi,1 Yeonjoo Kim,3 Sera Lee,4 Semi Kim,4 Min Soo Park1,5 1Department of Clinical Pharmacology, Severance Hospital, Yonsei University College of Medicine, Seoul, 2Department of Pharmaceutical Medicines and Regulatory Science, Colleges of Medicine and Pharmacy, Yonsei University, Incheon, 3Chong Kun Dang Clinical Research, Chong Kun Dang Pharmaceutical Corp., 4Chong Kun Dang Research Institute, Chong Kun Dang Pharmaceutical Corp., 5Department of Pediatrics, Yonsei University College of Medicine, Seoul, Republic of Korea Abstract: CKD-519 is a selective and potent cholesteryl ester transfer protein (CETP) inhibitor being developed for the treatment of dyslipidemia to raise high-density lipoprotein cholesterol. We investigated the safety, tolerability, pharmacokinetics, and pharmacodynamics of single doses of CKD-519 in healthy adult subjects. A randomized, double-blinded, placebo-controlled, single ascending dose study was performed. Eight healthy subjects were enrolled in each CKD-519 dose group (25, 50, 100, 200, or 400 mg) and randomized to CKD-519 (n=6) or matching placebo (n=2). CKD-519 reached the maximum plasma concentration (Cmax) at 5–6 h post-dose, and had a long terminal half-life ranging between 40–70 h. The area under the plasma concentration–time curve (AUC) and Cmax increased with the dose, however, Cmax and AUC normalized by dose decreased with each incremental dose. CETP activity decreased with dose, and the maximum decrease (63%–83%) was observed at 6–8 h post-dose. A sigmoid Emax model best described the relationship between CKD-519 plasma concentrations and CETP activity with an EC50 of 17.3 ng/mL. Overall, 11 adverse events (AEs) were observed. All AEs were mild or moderate in intensity, and resolved without any complications. There were no clinically significant effects on blood pressure. In conclusion, single doses of CKD-519 up to 400 mg were well tolerated and showed potent inhibition of CETP activity. Keywords: cholesteryl ester transfer protein inhibitor, CKD-519, pharmacokinetics, pharmacodynamics